Strategi Pemasaran Promo Beli Banyak Lebih Murah Alta Springbed di Lottemart Pakuwon - Ernawati, Ernawati; Kurniawati, Kurniawati; Zaman, Komarun (STIE PENA, 2023)
This study aims to find out the marketing strategy carried out by sales staff towards the promo to buy a lot cheaper Alta Springbed provided by Lottemart Lottemart Mall Pakuwon Center Surabaya. This study uses qualitative research methods with sales staff on duty at Lottemart Lottemart Mall Pakuwon Center Surabaya as informants or information providers. The results of this study indicate that there has been an increase in sales turnover of Alta Springbed from 2021 to 2022. The marketing strategy undertaken is to promote Alta Springbed through social media using internet technology and by serving consumers who come to Lottemart Pakuwon Trade Center. The main social media used is Facebook because social media Facebook is still in great demand by the public.